Adsorptive separation performance of 1-butanol onto typical hydrophobic zeolitic imidazolate frameworks (ZIFs). Issue 21 (10th May 2016) - Gao, Chunping; Shi, Qi; Dong, Jinxiang
Abstract : The performance of two hydrophobic zeolitic imidazolate frameworks, MAF-6 and TIF-1 Zn, in adsorptive separation of 1-butanol from acetone–butanol–ethanol model fermentation broth was studied and compared to the data reported for ZIF-8. Abstract : The performance of two hydrophobic zeolitic imidazolate frameworks, MAF-6 and TIF-1 Zn, in adsorptive separation of 1-butanol from acetone–butanol–ethanol model fermentation broth was studied and compared to the data reported for ZIF-8. It was found that, in single-component systems, the adsorption capacities of ZIF-8 and MAF-6 were larger than that of TIF-1 Zn, mainly because of their larger pore volume; however, the time necessary to reach equilibrium was shorter when TIF-1 Zn with a larger pore aperture was used. In breakthrough experiments, it was shown that the adsorptive separation mechanism on ZIF-8 and MAF-6 was based on combined thermodynamics and kinetic effects; on TIF-1 Zn, thermodynamic adsorption took place.